2020
DOI: 10.3390/cells9112429
|View full text |Cite
|
Sign up to set email alerts
|

Identification of New Genetic Clusters in Glioblastoma Multiforme: EGFR Status and ADD3 Losses Influence Prognosis

Abstract: Glioblastoma multiforme (GB) is one of the most aggressive tumors. Despite continuous efforts to improve its clinical management, there is still no strategy to avoid a rapid and fatal outcome. EGFR amplification is the most characteristic alteration of these tumors. Although effective therapy against it has not yet been found in GB, it may be central to classifying patients. We investigated somatic-copy number alterations (SCNA) by multiplex ligation-dependent probe amplification in a series of 137 GB, togethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…A recent study by Navarro et al reported a strong association between EGFR amplification (or EGFRvIII expression) and ADD3 copy number variations in GBM. Genetic clustering suggested the co-occurrence of both events in a subgroup of GBM, the cluster where patients were presented with the shortest survival ( 34 ). In accordance with this finding, GBMs with EGFR amplification are often accompanied by the complete loss of chromosome 10 and are considered the common phenotypic endpoint of different genetic pathways ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Navarro et al reported a strong association between EGFR amplification (or EGFRvIII expression) and ADD3 copy number variations in GBM. Genetic clustering suggested the co-occurrence of both events in a subgroup of GBM, the cluster where patients were presented with the shortest survival ( 34 ). In accordance with this finding, GBMs with EGFR amplification are often accompanied by the complete loss of chromosome 10 and are considered the common phenotypic endpoint of different genetic pathways ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…EGFR amplifications, commonly observed in GBM, have been shown by Matini et al to promote angiogenesis and vascular proliferation within the tumor [40] and are associated with poor survival [40,41]. Drugs that could block the EGFR pathway could, therefore, be useful in the treatment of GBM [40].…”
Section: Egfrmentioning
confidence: 99%
“…Navarro et al [18] showed that EGFRvIII mutation and ADD3 loss were bad prognostic markers in a series of glioblastomas studied by multiplex ligation-dependent probe amplification. From this result, we might understand the absence of effect of the inhibitors of receptor tyrosine kinases in those glioblastomas that do not present EGFR mutations.…”
mentioning
confidence: 99%